KERAGAAN PENYAKIT PADI PADA VARIETAS UNGGUL BARU UNTUK AGROEKOSISTEM RAWA DAN LAHAN KERING - Dini Yuliani; Johanes Amirrullah; - Sudir (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2017)
Swampand dryland agroecosystems has the potential tobe used as acomplementary effort to improve national food security. This effort washamperedby the disruption of plant disease in new improved varieties of riceasone of the technology to increase rice production. This study aims to determine the performance of rice diseases at new improved varieties for swamp and dryland agro eco systems. Research conducted in 2013 growing season in ICR Rusinga randomized block design with 3 replications. The treatments were13new improved varietiesi.e. Inpara 1, Inpara 2, Inpara 3, Inpara 4, Inpara 5, Inpara 6, Inpara 7, Inpago 4, Inpago 4, Inpago 5, Inpago 6, Inpago 7, Inpago 8, and Inpago 9. For disease survei llance drawn diagonalline in each experimental plot, each diagonalline taken10 samples of plant clumps. Each sample clumps was observed the disease severity that were found by scoring method (IRRI, 2002).The results showed there were six diseases that infect new improved varieties for swampand upland agro ecosystems name lystem rot, sheath blight, red stripe, cercosporaleaf spot, bacterial leaf blight,and bacterialleafstreak. Stem rot with the highest severity found in Inpara3(35.18%) and Inpago4(32.96%). Sheath blight with the highest severity found in Inpara1(6.11%) and Inpago7(5.74%). Red stripe withthe highests everity found in Inpara6 (47.78%) and Inpago9 (40.74%). Cercosporaleaf spotwiththe highestseverity found in Inpara5(40.37%) and Inpago6 (14.82%). Bacterial leaf blight with the highest severity found in Inpara3(24.26%) andInpago9 (32.04%). Bacterial leaf streak with the highest severity found in Inpara3(9.26%) and Inpago6 (30.56%).